(untitled) (People’s Journal of Management, 2025)
This study aimed to examine the tenure effect on organizational performance and the moderating impact of tenure between HRM practices and organizational performance. 2251 officer-level employees of nine Nepalese public financial institutions were the population. Among them, 430 was the sample size. The purposive sampling method was used to select the sample. One-way ANOVA has been used to assess differences in organizational performance among tenure levels (less than 5 years, 5-10 years, and more than 10 years). Process Macro Model One (1) has been used to test the moderating effect of tenure on the relationship between HRM practices and organizational performance. The result unveiled that organizational performance significantly differs among the tenure levels of more than 10 years, 5-10 years, and less than 5 years. Tenure moderated the association between HRM practices and organizational performance in Nepal’s public financial institutions.